ANALISIS PENGENDALIAN KUALITAS PRODUK MIE DENGAN METODE STATISTICAL PROCESS CONTROL - Agustin, Annisa; Azis, Anton Mulyono (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2024)
CV Manunggal Jaya is a company engaged in food production in Bandung. The company, which produces noodles experiences product defects that exceed the company's tolerance limit. The purpose of this study is to determine quality control, factors that cause product defects, and the application of the Statistical Process Control (SPC) method. This research method is a descriptive quantitative method with data collection using interviews, observation and documentation. Data processing is done using tools such as flowchart, fishbone diagram, check sheet, histogram, control chart (p-chart) and pareto diagram. Based on the research results that there are 3 (three) quality controls, namely: Quality control of raw materials, production processes, finished products. Product defects are caused by human factors, raw materials, machines, and methods. There are three types of defects that occur at CV Manunggal Jaya Bandung, namely size defects, texture defects and dirty dough. Based on the results of the control chart (p-chart), it is known that the CL is 0.0081, UCL is 0.00961, LCL is 0.00668. The results of the analysis using the Pareto diagram tool state that the priority of improvements that must be made by the company is on texture defects.